Avulsion of the Lateral Head of the Gastrocnemius in a Dog: Surgical Treatment and an Ex Vivo Study on Pathomechanisms - Roses, Leonor; Arnott, Davinia (VCOT Open, 2022)
A 6-year-old Border Collie presented with a 4-month history of progressive plantigrade stance of the right hindlimb, following a jump when chasing a ball. Avulsion of the lateral head of the gastrocnemius and tearing of the medial muscular belly were confirmed radiographically and ultrasonographically. Surgical repair of the lateral head was performed using two nylon mattress sutures placed around the fabella and through femoral condylar bone tunnels, followed by the application of a cranial half cast for 5 weeks. No complications were reported and follow-up owner's questionnaire at 18 months postoperatively revealed excellent results with the dog returning to normal activity.Avulsion of the lateral fabella was induced in a cadaveric limb and hyperflexion of the tarsus was simulated. Extreme hyperflexion of the tarsus only occurred once a subsequent tear of the medial belly of the gastrocnemius had developed, but without avulsion of the medial fabella.
Keywords: gastrocnemius; avulsion; lateral head; leader line; cadaver